Neuropathic Donor-Site Pain following Radial Forearm Free Flap Harvest: A Multicenter Study on Incidence, Prognostic Factors, and Quality of Life - Bruin, L. L.; Hundepool, C. A.; Duraku, L. S.; Luijsterburg, A. J. M.; Jong, T. De; Willems, W. F.; Mureau, M. A. M.; Zuidam, J. Michiel (Journal of Reconstructive Microsurgery, 2022)
Background The radial forearm free flap (RFFF) is widely used and is considered one of the workhorse flaps in oncologic head and neck reconstructions. However, the potential for significant donor-site morbidity remains a major drawback. Although various donor-site problems have been reported, the incidence of neuropathic pain and possible predicting factors remain unclear. This study aimed to identify the incidence, prognostic factors, and impact on quality of life of neuropathic pain following RFFF harvest.Methods In this multicenter, cross-sectional study, 167 patients who underwent an RFFF reconstruction between 2010 and 2020 were included. Baseline characteristics were collected by medical charts. All patients received questionnaires to measure patient's pain (Doleur Neuropathique 4 and visual analog scale, pain), hand function (Patient-Reported Wrist and Hand Evaluation), and quality of life (EuroQol 5D). Multiple logistic regression was used to identify prognostic factors associated with outcomes.Results A total of 114 patients (68%) completed the questionnaire. Neuropathic pain was present in 18% of all patients. Donor-site wound problems, mostly tendon exposure, occurred in 32% and was significantly correlated with neuropathic pain (p = 0.003). Neuropathic pain was significantly associated with poorer quality of life (p < 0.001) and poorer hand function (p < 0.001).Conclusion Almost one-fifth of all patients deal with neuropathic pain following RFFF harvest. Neuropathic pain is significantly correlated with poorer hand function and a poorer quality of life. Therefore, future research should focus on analyzing surgical factors such as the management of wound problems and primary denervation to improve hand function and quality of life of these patients.
Keywords: donor-site morbidity; peripheral; nerve; radial forearm free flap; neuropathic pain